Become a Python data analyst - Fuentes, Alvaro (Packt Publishing, 2017)
"The Python programming language has become a major player in the world of data science and analytics. This course introduces Python’s most important tools and libraries for doing data science; they are known in the community as 'Python’s data science stack'. This is a practical course where the viewer will learn through real-world examples how to use the most popular tools for doing data science and analytics with Python."--Resource description page.